Criminología vial: La construcción social de los siniestros viales a través del análisis de cinco agentes: Un estudio comparativo de las ciudades de León y Aguascalientes - Hernández Fernández, Francisco Israel (Archivos de criminología, seguridad privada y criminalística, 2020)
This work focuses its objective on five road agents: 1) motor vehicle drivers, 2) vehicle passengers, 3) pedestrians, 4) cyclists and 5) motorcyclists. All of them considered agents, at the time of matching in the accident and make up this first category of "road agents", only in the "hot spots" or "hot or red spots" of the most often sinister road space that make up the cities of Leon and Aguascalientes. The working method for this research analyses social action through the urban system, where the social practices of road agents are subjected to urban planning that cannot change, but can be appropriated; one cannot exist without the other. The urban system creates the road agent and the road agent recreates the urban system. Three major indicators are set out within the methodology: 1) Land transit events classified as road accidents, for which a definition of inclusion and exclusion was made; using statistical synthesis and geographic analysis to identify the points of both cities with greater road accidents (hot spots). The analysis tools were the databases and digital maps of them, disseminated by the National Institute of Statistics and Geography (INEGI). 2) Displacement guidelines and rules; This indicator made known the flows of road agents in the hot spots previously identified, according to the frequency of road accidents; so previously designed observation scripts and questionnaires were used, taking as guiding axes the mobility laws of both cities. 3) The construction of a road culture by road agents, understood as the meaning of urban reality in the road field and its relationship with the conduct of road agents, characterized by time and Primary Message Systems (MPS) developed by Hall (Hall, 1990) which provide a cultural explanation in the analysis of land transit events ending in road accidents.